Electricity Consumption Forecasting in the Age of Big Data - Xiaojia Wang (Institute of Advanced Engineering and Science, 2013)
In the age of big data, information mining technology has undergone tremendous change; traditional forecasting mining technology has not been able to solve the information mining problems under a large scale of data. this paper put forward a modeling mechanism of information analysis and mining under the age of big data, the modeling mechanism is, first, construct the model of task decomposition of information by MapReduce tool, then, make data preprocessing and mining operation according to the single task data sheet, use mathematical model, artificial intelligence and other methods to construct the new ideas of information analysis and data mining under the age of big data, finally, a case study presented to demonstrate the feasibility and rationality of our approach. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3278